The Understanding Improvement of Natural Science Concept of Primary School Teacher Education Department Students Using Project-Based Learning Model - Mustika, Dea; Ain, Siti Quratul (International Journal of Elementary Education, 2020)
Based on the results of observations, it was found that the understanding of the concept of students, especially elementary school science material, is very lacking, this is because the learning process is still dominated by presentations and does not provide opportunities for students to explore their own knowledge. This study aims to describe the application of the project based learning model to improve students' conceptual understanding. This research is a  classroom action research . The subjects of this study were students of the fourth semester class B which consist of 49 students. Data collection methods in the form of tests and non-tests with the instruments used were observation sheets and test questions. The pre-cycle test results obtained an average value of 64.8 with 47% classical completeness, in the first cycle the average value increased by 74.3 with 74% classical completeness and in the second cycle the average value became 85 with 88% classical completeness. These results indicate that the application of the project-based learning model can improve students' conceptual understanding of elementary schools science materials.